Comparison of ropivacaine with ropivacaine and fentanyl in continuous epidural analgesia for postherpetic neuralgia: A STROBE-compliant retrospective study. Issue 22 (29th May 2020) - Kang, Hee Yong; Lee, Chung Hun; Choi, Sang Sik; Lee, Mi Kyoung; Park, Jong Sun; Oh, Jung Suk
Abstract : Abstract: Continuous epidural analgesia (CEA) using local anesthetics is frequently used to control herpes zoster pain and prevent postherpetic neuralgia (PHN). However, few studies have been conducted to determine the efficacy of epidural drugs administered as CEA to manage PHN. This retrospective study was designed to evaluate the effectiveness of CEA with ropivacaine alone or with ropivacaine and fentanyl for controlling pain caused by PHN. We reviewed the medical records of 71 patients. We studied 2 groups: epidural ropivacaine (ER; CEA with ropivacaine alone; n = 44) and epidural ropivacaine and fentanyl (Epidural ropivacaine and fentanyl (ERF); CEA with ropivacaine and fentanyl; n = 27). To evaluate pain, a numeric rating scale (NRS) was evaluated at 6 time points: immediately before the procedure (baseline NRS score); 1 hour after the procedure; 14 days after the procedure; and 1, 3, and 6 months after the procedure. Complication rates were recorded during CEA. We also investigated whether additional invasive procedures were needed due to insufficient pain control during the 6-month follow-up period. After adjusting for confounding variables, there were no significant differences in the NRS scores between the 2 groups at any time point. The adjusted odds ratio for additional invasive procedures within 6 months after CEA was 1.03-times higher in the ERF group than in the ER group, but this difference was not statistically significant (95% confidence interval: 0.33–3.23, P = .96). Rates of complication (dysuria, vomiting, nausea, itching sensation, and hypotension) during CEA were higher in the ERF group than in the ER group. However, the differences were not statistically significant. There was no difference in the management of pain in patients with PHN between the groups. Epidural administration of fentanyl with ropivacaine did not improve pain management when compared to ropivacaine alone. Although not statistically significant, the incidence of complications during CEA was higher in the opioid combination group. Abstract : Supplemental Digital Content is available in the text